2016
DOI: 10.3945/jn.115.224774
|View full text |Cite
|
Sign up to set email alerts
|

Coffee Consumption Increases the Antioxidant Capacity of Plasma and Has No Effect on the Lipid Profile or Vascular Function in Healthy Adults in a Randomized Controlled Trial

Abstract: Both coffees, which contained CGAs and were low in diterpenes and caffeine, provided bioavailable CGAs and had a positive acute effect on the plasma AC in healthy adults and no effect on blood lipids or vascular function. The group that did not drink coffee showed no improvement in serum lipid profile, FMD, BP, or NO plasma metabolites. This trial was registered at registroclinico.sld.cu as RPCEC00000168.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
68
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(74 citation statements)
references
References 45 publications
5
68
0
1
Order By: Relevance
“…In a large cross-sectional population-based survey, high coffee consumption was associated with reduced triglyceride levels [22], while in another study moderate coffee consumption was associated with increased triglyceride concentrations in men [23]. In an intervention study, however, coffee consumption did not affect the lipid profile [24]. The inconsistencies observed may partly be related to the differences in the types of coffee consumed.…”
Section: Coffee Consumption Was Not Associated With the Triglyceride-mentioning
confidence: 93%
“…In a large cross-sectional population-based survey, high coffee consumption was associated with reduced triglyceride levels [22], while in another study moderate coffee consumption was associated with increased triglyceride concentrations in men [23]. In an intervention study, however, coffee consumption did not affect the lipid profile [24]. The inconsistencies observed may partly be related to the differences in the types of coffee consumed.…”
Section: Coffee Consumption Was Not Associated With the Triglyceride-mentioning
confidence: 93%
“…Chlorogenic acid, one of the most important polyphenols to be found in coffee, has well-documented antioxidant properties and thus may inhibit the destructive effects of free radicals on neurons. The literature has suggested that neuroprotective activity of chlorogenic acid is the basis for further research on its use for therapeutic purposes [70, 75]. The amount of polyphenols in coffee depends on numerous factors, including their content in coffee beans and the method of brewing.…”
Section: Coffee: a Possible Mechanism Of Actionmentioning
confidence: 99%
“…HCAs may enhance cardiovascular health by exerting blood pressurelowering effects and by acutely improving the endothelial function [89,100,101]. Some studies suggest that chlorogenic acids may cause significant reductions in systolic and diastolic blood pressure [100,102,103], but other studies have instead reported a lack of significant blood pressure reduction [104][105][106]. The differences could be attributed to the antihypertensive effects of chlorogenic acids only occurring in subjects with mild hypertension and not in normotensives [88,107].…”
Section: Health Benefits Related To Intake Of Phenolic Acidsmentioning
confidence: 99%